Pengaruh Motivasi dan Budaya Organisasi Kerja terhadap Kinerja Karyawan Amil Zakat di Lembaga Dompet Dhuafa Republika Jakarta - Dimas, Fachmi; Rozali, Muhammad; Syaiful (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
This research was carried out at the Dompet Dhuafa Republika Foundation Philanthropy Institute by taking the topic of problems in initial observations of Organizational Culture, Work Motivation, and Performance of Zakat Amils, especially of Zakat Amils in Dompet Dhuafa, showing that there is a need for further improvement in Organizational Culture so that zakat amils can really embed the cultural values of the Dompet Dhuafa Organization. The purpose of this research is to find out and analyze the influence of Organizational Culture and Work Motivation on Amil Zakat's Performance at the Dompet Dhuafa Republika Foundation Philanthropic Institute. The methods used in this research are qualitative descriptive and associative methods. The sample in this research was obtained from Amil Zakat who is in the Dompet Dhuafa Republika Philanthropy Building, South Jakarta. The questionnaire has been designed using a Likert scale to obtain data from 3 research variables, namely Organizational Culture, Work Motivation and Employee Performance. Data analysis used Multiple Linear Regression with the help of the SPSS 21.00 program. The research results show that Organizational Culture and Work Motivation influence Amil Zakat's performance by 54.2%. Keywords: motivation, work organizational culture, performance